A human mimicking control strategy for robotic deburring of hard materials. Issue 9 (2nd September 2018) - Villagrossi, Enrico; Pedrocchi, Nicola; Beschi, Manuel; Molinari Tosatti, Lorenzo
ABSTRACT: This paper deals with the use of an industrial robot (IR) for the deburring of hard material items (i.e. cast iron items). The control strategies introduced in this paper aim to mimic the human behaviour during the manual deburring. On the basis of force feedback, provided from a 1-axis load cell, the nominal deburring trajectory is optimised and deformed making multiple repetitions. The deburring trajectory is repeated until completing the nominal deburring path. The removal of thin layers of materials allows the robot to operate at high feed rates avoiding spindle stall and without exciting elastics effects on the mechanical structure of the system. Furthermore, a method to automatically detect the force changepoints, related to the presence of a burr, without tuning force thresholds, is discussed. The human mimicking control strategy is compared with a standard industrial approach demonstrating a reduction of the task cycle time and an improvement of the finishing quality.